SDG 2030, Agenda 2063, Russia-Ukraine War and Africa’s Development Possibilities - Mimiko, N. Oluwafemi ‘Femi’ (ABUAD Journal of Social and Management Sciences, 2023)
Sustainable Development Goals (SDG 2030) and Africa’s Agenda 2063 address clearly defined collective development agendas, while the war in Ukraine relates to strategic management. This paper takes a look at these seemingly differing, yet related subjects in the overall context of the development aspirations of Africa. It argues that SDG 2030 and Agenda 2063, like the Millennium Development Goals (MDGs) before them, are basically efforts at strategic planning, and underscore the integrated nature of the global political economy. As well, the war in Ukraine, and its globally ramifying nature, demonstrate the logic of globalisation, which makes collective approach to the agenda of development imperative. While the highly disruptive orientation of the war is evident, the possibility of African countries taking advantage of some of its dimensions to deepen their location in the global supply chain exists. Such may, however, not be realisable outside of a nimble state system that Africa does not as yet present; a fact which also accounts for the very modest performance of the continent on the MDGs, SDG 2030, and Agenda 2063 initiatives. The expanding poverty net on the African continent is the most profound testimonial that Africa is still not acquitting itself creditably vis-à-vis these initiatives. The emergence and sustenance of an appropriately positioned developmental state is, therefore, a critical desideratum if the continent must moderate the massive disruptive impacts of the war in Ukraine, benefit from it where it can, and drive more determinedly towards the objectives of SDG 2030 and Agenda 2063.